2010
DOI: 10.1002/14651858.cd000984.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to change the behaviour of health professionals and the organisation of care to promote weight reduction in overweight and obese adults

Abstract: Background The prevalence of obesity is increasing globally and will, if left unchecked, have major implications for both population health and costs to health services. Objectives To assess the effectiveness of strategies to change the behaviour of health professionals and the organisation of care to promote weight reduction in overweight and obese people. Search methods We updated the search for primary studies in the following databases, which were all interrogated from the previous (version 2) search d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 79 publications
0
72
0
4
Order By: Relevance
“…The authors noted that practitioners' adherence to the intervention protocol was low, thus intensity could not be accurately estimated. Provider-targeted interventions for weight loss have been discussed in detail in other reviews (43)(44)(45) . While a structured protocol to assist practitioners with delivery of weight-loss counselling appeared effective in producing some weight loss in overweight or obese patients, none of the interventions reported achieving clinically significant weight loss, making it questionable whether physician-delivered interventions alone are worth implementing in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted that practitioners' adherence to the intervention protocol was low, thus intensity could not be accurately estimated. Provider-targeted interventions for weight loss have been discussed in detail in other reviews (43)(44)(45) . While a structured protocol to assist practitioners with delivery of weight-loss counselling appeared effective in producing some weight loss in overweight or obese patients, none of the interventions reported achieving clinically significant weight loss, making it questionable whether physician-delivered interventions alone are worth implementing in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…4,14,16,47,48 In a randomized controlled trial, 48 patients who had a prompt to calculate BMI in their electronic medical record were significantly more likely than patients without a prompt to receive a diagnosis of obesity (16.6% v. 10.7%; p = 0.016) and referrals for dietary (14.0% v. 7.3%, p = 0.002) and physical activity (12.1% v. 7.1%, p = 0.016) interventions. Furthermore, one trial found that reminders to perform specific preventive actions could change practice, resulting in a significant reduction in weight among men (by 11.2 kg, 95% CI 1.7 to 20.7 kg, at 1 year).…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, one trial found that reminders to perform specific preventive actions could change practice, resulting in a significant reduction in weight among men (by 11.2 kg, 95% CI 1.7 to 20.7 kg, at 1 year). 47 Compared with standard care, educational interventions aimed at changing the behaviour of health care professionals to promote weight reduction have been shown to be effective (level I evidence). Box 5 includes resources for primary care physicians.…”
Section: Reviewmentioning
confidence: 99%
“…Thus, it is crucial to raise stakeholders' awareness about the limitations of patients' willpower to prevent and reverse obesity, and thus the importance of treating obesity as a disease with appropriate treatment. Indeed, education of healthcare providers about overweight and obesity has been shown to change negative attitudes [96,99].…”
Section: Obesity Biasmentioning
confidence: 99%